The Effect of Briquettes Composition Made of Sago Dregs and Wood Chips to The Performa of Biomass Stove - Sulpa Rosadi; Jhonni Rahman; Eddy Elfiano; Yose Rizal (Aptek, 2023)
Sago dregs and wood chips are types of agricultural and industrial waste that have economic value to be converted into alternative energy, namely briquettes. The purpose of this research was to determine the effect of variations in the raw material composition of sago dregs and wood chips to the performa of biomass stoves. In this research, the composition used were 100% sago dregs, 70% sago dregs mixed with 30% wood chips, 50% sago dregs mixed with 50% wood chips, 70% sago dregs mixed with 30% wood chips and 100% wood chips, 5 variation of composition. The Briquettes was compressed with a load of 2 kg. The test was carried out by burning briquettes in a semi-gasification biomass stove reactor. In testing the performance of biomass stoves, we can see that the highest burning rate is found in the 100% wood chips variation with a burning rate of 0.00029 kg/s. And the highest output power is found in the 100% wood chips variation with an output value of 7.45 kJ/s. And the highest density before and after drying the tar can be found in the 100% wood chips variation with values ​​of 0.125 gr/cm^3 and 0.90 gr/cm^3. And the highest efficiency is found in the 100% wood chips variation with an efficiency value of 17.11%. And the highest calorific value is found in the 100% wood chips variation with a calorific value of 6108.57 cal/gram.